Photostability of acetylated wood coated with nano zinc oxide - B. Nagarajappa, Giridhar; Nair, Sreeja; Srinavas, Kavyashree; N. Subba Rao, Anantha; K. Pandey, Krishna (Maderas. Ciencia y Tecnología, 2020)
Chemical modification with acetic anhydride is an effective method to stabilise wood against dimensional movement and improve decay resistance of wood. It has also been reported to retard UV light induced color darkening on wood surface. Coatings of wood surfaces with certain nano metal oxides have also shown promise as UV screening agent. In this work, we have evaluated synergistic effect of acetylation of wood and application of nano material on wood surfaces to enhance their UV stability. Photo-stability of acetylated Wrightia tinctoria wood coated with zinc oxide (ZnO) nanodispersion was evaluated by irradiating these wood specimens to UV radiation in an accelerated weathering tester. Acetylation of wood with acetic anhydride exhibited photo-bleaching and inhibited light-induced color darkening observed in unmodified wood. Coating of unmodified and modified wood surfaces with ZnO nanodispersion reduced photo-discolouration and degradation of wood polymers. The photo-bleaching observed in chemically modified wood upon light irradiation was further enhanced by application of nano coating on wood surfaces.